Managing apple maggot, Rhagoletis pomonella [Diptera : Tephritidae], by perimeter trapping - Bostanian, N.J.; Vincent, C.; Chouinard, G.; Racette, G. (Phytoprotection, 1999)
Perimeter trapping is an effective physical method to control apple maggot (Rhagoletis pomonella) in apple (Malus pumila) orchards. It provided 99.5 to 100 % clean fruit at harvest in commercial orchards. The traps were red spheres (9 cm diam) or yellow boards (28 cm x 21.5 cm) sandwiched between the two halves of red spheres. They were coated with a sticky material and baited with butyl hexanoate. The number of traps per plot was a function of the length of the plot facing a possible entry site of R. pomonella. In plots adjacent to forest, traps were placed at ca. 10 m intervals on the row, or on the outer most tree of every row. Sides of plots adjacent to prairie grass or a chemically-treated plot had traps at approximately 20-m intervals. To achieve commercially acceptable apple maggot control, the activity of the pest should be low to moderate. Susceptiblity to apple maggot attack varied from one apple cultivar to another. Therefore, this criterion should be considered when perimeter trapping of apple maggot is envisaged.